Characterising Bilateral Trade between sub-Saharan Africa and China: The Specific Role of Institutional Quality - (:unkn) unknown (My University, 2021)
A new dimension of international trade has appeared in past decades with the awakening of South-South trade, mainly driven by China. The so-called “Chinese move into Africa” phenomenon is one of the main characteristics of this economic mutation. This paper aims at exploring the determinants of the upsurge of bilateral trade between sub-Saharan Africa (SSA) and China but with a special focus on the role of institutions. To this regard, we applied a theoretically consistent structural gravity model to a worldwide database covering the period 1996-2012. We built specific interaction variables to study how the sino-African trade is influenced by the institutional channel of African countries both measured by the political regime and the governance quality. The main results indicate that in the context of China-SSA trade flows, a democratic regime is pro-trade but surprisingly an improvement in control of corruption leads to deteriorate trade. More generally, institutional quality (except for control of corruption) is important to boost Chinese exports to SSA but does not seem to be a necessary requirement for African exports to China. Accordingly, in the extent that institutional reforms take time to operate, trading with China could be an interesting medium-run opportunity for SSA to pursue its growth and development process.
Keywords: African Research